Capsids and Genomes of Jumbo-Sized Bacteriophages Reveal the Evolutionary Reach of the HK97 Fold - Jianfei Hua (American Society for Microbiology, 2017)
ABSTRACT Large icosahedral viruses that infect bacteria represent an extreme of the coevolution of capsids and the genomes they accommodate. One subset of these large viruses is the jumbophages, tailed phages with double-stranded DNA genomes of at least 200,000 bp. We explored the mechanism leading to increased capsid and genome sizes by characterizing structures of several jumbophage capsids and the DNA packaged within them. Capsid structures determined for six jumbophages were consistent with the canonical phage HK97 fold, and three had capsid geometries with novel triangulation numbers (T=25, T=28, and T=52). Packaged DNA (chromosome) sizes were larger than the genome sizes, indicating that all jumbophages use a head-full DNA packaging mechanism. For two phages (PAU and G), the sizes appeared very much larger than their genome length. We used two-dimensional DNA gel electrophoresis to show that these two DNAs migrated abnormally due to base modifications and to allow us to calculate their actual chromosome sizes. Our results support a ratchet model of capsid and genome coevolution whereby mutations lead to increased capsid volume and allow the acquisition of additional genes. Once the added genes and larger capsid are established, mutations that restore the smaller size are disfavored. IMPORTANCE A large family of viruses share the same fold of the capsid protein as bacteriophage HK97, a virus that infects bacteria. Members of this family use different numbers of the capsid protein to build capsids of different sizes. Here, we examined the structures of extremely large capsids and measured their DNA content relative to the sequenced genome lengths, aiming to understand the process that increases size. We concluded that mutational changes leading to larger capsids become locked in by subsequent changes to the genome organization.